2022
DOI: 10.1039/d2sc01832b
|View full text |Cite
|
Sign up to set email alerts
|

Aqueous electrochemically-triggered atom transfer radical polymerization

Abstract: Simplified electrochemical atom transfer radical polymerization (seATRP) using CuII-pyridineimine complexes is reported and follows a previously unreported electrochemically triggered mechanism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 54 publications
0
9
0
Order By: Relevance
“…Under continuous electrolysis conditions polymerization of oligo(ethylene glycol) methyl ether methacrylate (M n = 300 g.mol -1 ; OEGMA 300 ) yielded POEGMA with good control over molecular weight distribution (Đ m < 1.35). 99 Interestingly, these polymerizations are not under complete electrochemical control, as monomer conversion continues when electrolysis is halted during reactions in which sequentially steps of applied potential and no applied potential are performed.…”
Section: Polymer Chemistry Accepted Manuscriptmentioning
confidence: 99%
See 2 more Smart Citations
“…Under continuous electrolysis conditions polymerization of oligo(ethylene glycol) methyl ether methacrylate (M n = 300 g.mol -1 ; OEGMA 300 ) yielded POEGMA with good control over molecular weight distribution (Đ m < 1.35). 99 Interestingly, these polymerizations are not under complete electrochemical control, as monomer conversion continues when electrolysis is halted during reactions in which sequentially steps of applied potential and no applied potential are performed.…”
Section: Polymer Chemistry Accepted Manuscriptmentioning
confidence: 99%
“…Under continuous electrolysis conditions polymerization of oligo(ethylene glycol) methyl ether methacrylate ( M n = 300 g mol −1 ; OEGMA 300 ) yielded POEGMA with good control over molecular weight distribution ( Đ m < 1.35). 99 Interestingly, these polymerizations are not under complete electrochemical control, as monomer conversion continues when electrolysis is halted during reactions in which sequentially steps of applied potential and no applied potential are performed. Alternatively, it was shown that the extent and rate of polymerization depends upon an initial period of electrolysis with seATRP using Cu II (NAPI) 2 following an electrochemically-triggered, rather than electrochemically mediated, ATRP mechanism (Fig.…”
Section: Radical Chain-growth Polymerizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Low catalyst loading methods offer more environmentally benign and industrially scalable reaction conditions compared to "classical" ATRP but also provide an option to prepare polymers with designed dispersity, defined by the catalyst content (Discekici et al 2018(Discekici et al , 2016(Discekici et al , 2017Lu et al 2019;Matyjaszewski 2012a;Parkatzidis et al 2020;Treat et al 2014). The new low ppm ATRP methods regenerate the activator by the use of a chemical reducing agent as a radical initiator in initiators for continuous activator regeneration (ICAR) ATRP (Konkolewicz et al 2012;Luan et al 2022), chemical compounds (Luo et al 2022;Matyjaszewski et al 2007;Min et al 2007) and silver (Williams et al 2015) in activators regenerated by electron transfer (ARGET) ATRP-used a few times for membrane modification (Bhut et al 2012;Worthley et al 2011), zerovalent metals in supplemental activator and reducing agent (SARA) ATRP (Chmielarz et al 2015a;Konkolewicz et al 2014Konkolewicz et al , 2013, external stimuli as an electrical current in electrochemically mediated ATRP (eATRP) (Chmielarz 2017;Chmielarz et al 2015b;De Bon et al 2022;Han et al 2022;Park et al 2015;Zhao et al 2022), light in metal-free (Soly et al 2022;Su et al 2022;Treat et al 2014) or photochemically mediated ATRP (photo-ATRP) (Fu et al 2021;Huang et al 2017;Tasdelen et al 2011), mechanical forces in mechanically induced ATRP (mechano-ATRP) (Liu et al 2022a;Mohapatra et al 2018;Wang et al 2019), ultrasound in ultrasonication-induced atom tran...…”
Section: Fundamentals Of Flat Surfaces Modification: Atom Transfer Ra...mentioning
confidence: 99%
“…The once complex reaction set up of eATRP has been simplified over the last 10 years, to a point where eATRP can performed in a 'plug-and-play' configuration using commercial, standardised equipment (IKA ElectraSyn). 22,23 Furthermore, it can be run in 2-electrode configuration, by virtue of the use of sacrificial counter electrodes (CE), in an undivided electrochemical cell using cheap and easy to operate current generators in simplified eATRP (seATRP) under galvanostatic (constant current) conditions. 24 Both potentiostatic (constant potential) and galvanostatic eATRP have been mainly used for the controlled polymerisation of (meth)acrylates, in both organic [25][26][27] and aqueous [28][29][30] media.…”
Section: Introductionmentioning
confidence: 99%